Effect of adipose‐derived stromal cells and BMP12 on intrasynovial tendon repair: A biomechanical, biochemical, and proteomics study. Issue 4 (14th October 2015) - Gelberman, Richard H.; Shen, Hua; Kormpakis, Ioannis; Rothrauff, Benjamin; Yang, Guang; Tuan, Rocky S.; Xia, Younan; Sakiyama‐Elbert, Shelly; Silva, Matthew J.; Thomopoulos, Stavros
ABSTRACT: The outcomes of flexor tendon repair are highly variable. As recent efforts to improve healing have demonstrated promise for growth factor‐ and cell‐based therapies, the objective of the current study was to enhance repair via application of autologous adipose derived stromal cells (ASCs) and the tenogenic growth factor bone morphogenetic protein (BMP) 12. Controlled delivery of cells and growth factor was achieved in a clinically relevant canine model using a nanofiber/fibrin‐based scaffold. Control groups consisted of repair‐only (no scaffold) and acellular scaffold. Repairs were evaluated after 28 days of healing using biomechanical, biochemical, and proteomics analyses. Range of motion was reduced in the groups that received scaffolds compared to normal. There was no effect of ASC + BMP12 treatment for range of motion or tensile properties outcomes versus repair‐only. Biochemical assays demonstrated increased DNA, glycosaminoglycans, and crosslink concentration in all repair groups compared to normal, but no effect of ASC + BMP12. Total collagen was significantly decreased in the acellular scaffold group compared to normal and significantly increased in the ASC + BMP12 group compared to the acellular scaffold group. Proteomics analysis comparing healing tendons to uninjured tendons revealed significant increases in proteins associated with inflammation, stress response, and matrix degradation. Treatment with ASC + BMP12 amplified these unfavorable changes. In summary, the treatment approach used in this study induced a negative inflammatory reaction at the repair site leading to poor healing. Future approaches should consider cell and growth factor delivery methods that do not incite negative local reactions. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:630–640, 2016.